THE INFLUENCE OF CHARISMATIC LEADERSHIP STYLE, CLARITY OF COMMUNICATION AND WORK ENVIRONMENT ON WORK MOTIVATION - Christine Christine; Hasyim Hasyim; Anastina Tahjoo (CV. Bunda Ratu, 2023)
Work motivation is a force that encourages employees to behave, directing behavior according to their abilities in a goal-oriented manner by involving themselves in work. The strength and weakness of a worker's work motivation also determines the size of his or her achievements. Based on the results of the observations made, it appears that there are still obstacles related to communication, the role of the unit head and the work environment, which influences employee work motivation. The aim of this research is to analyze the influence of the work environment, clarity of communication and leadership style on work motivation both simultaneously and partially. This research uses a descriptive statistical method with a correlational associative quantitative approach and a survey method using a questionnaire. The sampling technique used systematic random sampling with a total of 157 permanent employees from nursing and medical support units. This research uses multiple linear regression tests. Based on the results of the regression analysis, it was found that the variable value of communication clarity had the most influence on employee work motivation. The results of data analysis and hypothesis testing state that simultaneously and partially there is a significant influence between the work environment, clarity of communication and leadership style on work motivation .